2015
DOI: 10.1038/nchem.2258
|View full text |Cite
|
Sign up to set email alerts
|

A molecular shuttle that operates inside a metal–organic framework

Abstract: A 'molecular shuttle' is an interlocked molecular assembly in which a macrocyclic ring is able to move back and forth between two recognition sites. This large-amplitude translational motion was first characterized in solution in 1991. Since that report, many mechanically interlocked molecules (MIMs) have been designed, synthesized and shown to mimic the complex functions of macroscopic switches and machines. Here, we show that this fundamental concept-the translational motion of a molecular shuttle-can be org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
212
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(219 citation statements)
references
References 47 publications
4
212
0
3
Order By: Relevance
“…Because of their crystallinity and tunability, MOFs are an ideal scaffold on which to organize machine subunits and tune their response to stimuli. Notably, Zhu et al (23) used a [2] rotaxane molecular switch as a building block in a MOF to construct a conceptual molecular machine.…”
mentioning
confidence: 99%
“…Because of their crystallinity and tunability, MOFs are an ideal scaffold on which to organize machine subunits and tune their response to stimuli. Notably, Zhu et al (23) used a [2] rotaxane molecular switch as a building block in a MOF to construct a conceptual molecular machine.…”
mentioning
confidence: 99%
“…Earlier this year, Robert Schurko and Stephen Loeb of the University of Windsor, Canada, showed that they could pack about 10 21 molecular shuttles into each cubic centimetre of a MOF 4 . And last month, Stoddart unveiled 5 a different MOF that contained switchable rotaxanes.…”
Section: Shuttle Launchmentioning
confidence: 99%
“…The biological molecular transport systems consist of two major parts: the cytoskeleton and motor proteins [233,234]. The functions of intracellular motor-proteins inspired the engineering molecular motors [235,236]. The advance in the design of artificial molecular motors promotes the understanding of the mechanism of intracellular transport [112,202,237,238].…”
Section: Biological Transport Information Processing and Cognitive mentioning
confidence: 99%